Adolescent alcohol- and illicit drug-use in first and second generation immigrants in Sweden - Mikael Svensson; Curt Hagquist (Örebro University School of Business, 2009)
In this paper adolescent alcohol- and illicit drug-use among 1st and 2nd generation immigrants from Nordic, non-Nordic European and non-European countries were compared with the Swedish majority population. Multilevel logistic regression analysis was performed based on survey data from three different Swedish regions including 24 municipalities sampled in 2005 including 13,070 adolescents. Immigrants from Nordic countries were more likely to use alcohol (OR: 1.10-1.37) while immigrants from non- European countries were less likely to use alcohol (OR: 0.52-0.81), mainly explained by the relatively low use by girls from non-European countries. All immigrant groups were more likely to use illicit-drugs compared to the majority population. Highest drug-use were found among first generation Nordic Immigrants (OR: 3.15-4.17) and non-European immigrants (OR: 2.92-3.13). Consumption patterns among second generation immigrants were more similar to the Swedish majority population, implying more alcohol-use and less illicit drug-use.
Keywords: I12; I18; J15; 330; alcohol; drug use; ethnicity; immigrants; adolescents